Tinjauan Hukum Islam Terhadap Tes Urine dalam Mengidentifikasi Penyalahgunaan Narkotika dan Psikotropika di BNP Jawa Timur - Siti Nur Suciowati (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
This paper is field research conducted at BNP East Java. This study aims to find: (1) conducting urine tests at BNP East Java and their significance, and (2) Islamic law's perspective on urine tests in identifying narcotics and psychotropic abuse. The results of the study concluded that: first, the urine test consists of three stages: firstly, a person must urinate and put in a container; secondly, the officer starts checking and finally determining the results. According to Islamic law, urine tests in identifying narcotics and psychotropic abuse are allowed on condition that all equipment must be washed and cleaned with water. The problem of proving the narcotics and psychotropic misuse is oriented towards the objectives of Islamic law without undermining the problem of urine that is unclean objects. The verification process is aimed to generate benefit by upholding justice so that a secure and peaceful society is formed. On the other hand, urine is one of the unclean objects and must be purified.